2018
DOI: 10.21037/jtd.2017.11.130
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effects of N-acetylcysteine alone and combined with tigecycline on planktonic cells and biofilms of Acinetobacter baumannii

Abstract: NAC alone significantly inhibited biofilm formation of . The combination of NAC and TGC induced partial synergistic effect against planktonic cells and synergistic effect against biofilm-embedded, which might be a therapeutic option for biofilm-related infections of .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…It has yet to be determined if variability in biofilm production affects treatment or clinical outcome. Although several studies have reported on biofilm treatment agents, they have not specified differences in efficacy of agents on isolates that have produced high, moderate or low biofilm production . This is an area that future studies may clarify.…”
Section: Discussionmentioning
confidence: 99%
“…It has yet to be determined if variability in biofilm production affects treatment or clinical outcome. Although several studies have reported on biofilm treatment agents, they have not specified differences in efficacy of agents on isolates that have produced high, moderate or low biofilm production . This is an area that future studies may clarify.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its mucolytic activity, NAC has attracted microbiologists to explore its potential as an antibacterial and antibiofilm agent. A number of in vitro studies assessed the activity of NAC against different Gram positive and Gram-negative bacteria including Escherichia coli, Acinetobacter baumannii, Pseudomonas aeruginosa, Klebsiella pneumoniae, Staphylococcus aureus, and Staphylococcus epidermidis amongst others (Quah et al,2012; Choi et al,2018; Feng et al,2018; Jun et al,2019; Ciacci et al, 2019; Li et al,2020; Guerini et al,2020; Kundukad et al, 2020; Manoharan et al, 2021). Given the broad-spectrum activity of NAC against bacteria, this study aims at repurposing N-acetyl cysteine (NAC) to treat biofilms of XDR K. pneumoniae , isolated from patients in hospitals.…”
Section: Introductionmentioning
confidence: 99%